Voltammetric sizing of particles: chronoamperometry of impact events in acoustically agitated particulate suspensions. - Rees, N; Compton, R (2007)
This communication presents initial results into the use of chronoamperometry of acoustically agitated particulate suspensions at a dual electrode as a means of approximately sizing the suspended particles.